Analysis of Peer Conformity in Reference to Moderate Religiosity for The Development of Christian Education of GMIM Christian Junior High School Students in Manado - Sumakul, Yunita; Lolombulan, Julius; Weol, Wolter (Peneliti.net, 2024)
Throughout adolescence, a peer group is very important for teenagers. To be accepted in the group, they try to adapt to the values and rules of the group, including moderate religious behavior. This study aims to analyze peer conformity in relation to students' moderate religiosity as an essential component in the development of Christian religious education. This study was conducted on 219 students at four GMIM Christian Junior High Schools in Manado. It applied a correlational quantitative approach with a survey method. Before being distributed to the respondents, the questionnaire was tested on 30 students and tested for its validity and reliability. According to the result, the questionnaire was revised and distributed to the respondents. The value of the relationship between peer conformity and students’ moderate religiosity was Sig. = 0,001 < = 0,05 and the value of correlation coefficient was 0,952. It indicated that there was a very strong and significant correlation between peer conformity and students’ moderate religiosity. The result showed that there was an influence from the peer conformity variable on moderate religiosity variables with a significant value ρ = 0,001 which was smaller than the set alpha value α = 0,05 (ρ = 0,001 < 0,05). Peer conformity had an influence of 54,7% on students’ moderate religiosity.